Collision Carcinoma Involving Small Cell Neuroendocrine Carcinoma and Squamous Cell Carcinoma of the Ureter: A Case Report and Review of the Literature - Xu, Sheng; Xu, Lei; Cao, Peng; Yao, Shiyun; Wu, Tingming; Hu, Xinming; Chen, Hualei; Gu, Jun; Che, Xianping (Frontiers in Oncology, 2021)
Background: Small cell neuroendocrine carcinoma (SCNEC) of the ureter is a rare tumour, accounting for less than 0.5% of all ureteral tumours. SCNEC tumours are highly aggressive and patients have a poor prognosis. Ureteral SCNEC colliding with other pathological types of tumours is extremely rare. In this paper, we present the case of a patient with ureteral small cell carcinoma colliding with squamous cell carcinoma and review the literature regarding the clinicopathological features, treatment and prognosis of thus tumour. To the best of our knowledge, this is the second identified case of ureteral SCNEC colliding with SCC. Case Presentation: A 64-year-old male patient presented with a history of 1 month of gross haematuria and 3 months of left flank pain. CT urography revealed a soft tissue mass in the upper ureter, which was slightly enhanced on contrast-enhanced CT. Nephroureterectomy was performed after the patient was diagnosed with a tumour in the left ureter. Microscopy and immunohistochemical examination confirmed the mass to be a SCNEC collision with SCC. Two months after the surgery, the patient received adjuvant chemotherapy (cisplatin/etoposide). After 14 months of follow-up, no local recurrence or distant metastasis was found. Conclusion: Ureteral collision carcinoma with SCNEC predominantly occurs in Asian individuals, is difficult to diagnose preoperatively and is highly invasive. The current management of ureteral collision carcinoma is a comprehensive treatment based on surgery.